Industrial networks: are they a new and alternative way to conduct business or just a logical consequence of a globalising economy? - Siebler, Vanessa (2012)
Based on a report for the seminar Industrial Networks, at Goethe Universität Frankfurt am Main Dozent: Prof. Dr. Blättel-Mink, Prof. Dr. António Moniz SS 2011